The Concept Developing a Simplified Accounting System for Small Businesses - Zhurakovska, Iryna (Herald of Economics, 2026)
This article is devoted to the theoretical justification and development of a concept for establishing a simplified accounting system for small businesses in the context of a growing regulatory burden and the digital transformation of the economy. The relevance of the research stems from the fact that the current accounting model in Ukraine is largely geared towards the needs of large businesses, leading to disproportionately high costs of accounting and tax compliance for small enterprises. The paper demonstrates the existence of a disparity between the costs of organising accounting and the managerial value of the information generated for small business owners. The aim of the study is to provide a theoretical justification for the conceptual foundations of reforming the accounting system for small businesses and to identify priority areas for its simplification, taking into account the limited resources of small businesses. The methodological basis of the study was formed by methods of comparative analysis, abstraction, modelling, the engineering approach and the method of essentialism, which enabled the development of an approach to organising accounting based on the principle of ‘less volume — higher-quality data’. The article systematises the key areas of development in accounting for small businesses: institutional, tax and accounting, globalisation, digital, and environmental, social and governance (ESG). It has been established that, in the short term, the priority areas for small businesses are tax and fiscal matters and digitalisation, which help to minimise accounting costs and enhance the transparency of financial transactions. Based on an analysis of international and national research, the most common recommendations for simplifying accounting have been summarised, in particular the use of historical cost, the convergence of financial and tax accounting, and the use of automated digital services. A conceptual model of a simplified accounting system for small businesses has been developed, which provides for the minimisation of accounting procedures, a reduction in the number of registers and documents, maximum automation of data processing, and integration with banking and tax digital services. The main principles of such a system’s operation have been identified: simplicity, clarity, sufficiency, flexibility, accessibility and digitalisation. It has been demonstrated that the implementation of the proposed model can significantly reduce the administrative burden on entrepreneurs, cut the time spent on record-keeping and increase the transparency of financial results. The practical value of the study lies in the possibility of using the proposed concept when drafting regulatory acts on reforming the accounting system for small businesses, as well as in the process of further digitalisation of interaction between business and the state.